2015
DOI: 10.1017/s0958344015000075
|View full text |Cite
|
Sign up to set email alerts
|

Mobile technology in second language classrooms: Insights into its uses, pedagogical implications, and teacher beliefs

Abstract: Mobile technology in second language classrooms: Insights into its uses, pedagogical 1 implications, and teacher beliefs. Abstract 12Adopting a multiple-case, multiple-method design, this study investigates mobile technology 13 use in the practices of three experienced second language teachers. The findings, based on an 14 analysis of the teachers' rationales, stated beliefs and classroom actions, show that the 15 teachers tend to prohibit or reluctantly tolerate mobile device usage, while they recognise 16 so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 19 publications
(31 reference statements)
0
19
0
1
Order By: Relevance
“…Finally, results indicated that teachers assigned value to the use of iPads and mobile apps to support curriculum goals, pedagogy, and student outcomes despite the fact that they occasionally served as distraction. Other studies also noted that teachers considered mobile devices to be a distraction for students (Praag & Sanchez, ). Unlike earlier studies, however, which documented dissatisfaction with one‐to‐one initiatives after the first year (e.g., Swallow, ), teachers in this study remained committed to mobile learning.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, results indicated that teachers assigned value to the use of iPads and mobile apps to support curriculum goals, pedagogy, and student outcomes despite the fact that they occasionally served as distraction. Other studies also noted that teachers considered mobile devices to be a distraction for students (Praag & Sanchez, ). Unlike earlier studies, however, which documented dissatisfaction with one‐to‐one initiatives after the first year (e.g., Swallow, ), teachers in this study remained committed to mobile learning.…”
Section: Discussionmentioning
confidence: 97%
“…Unlike earlier studies, however, which documented dissatisfaction with one‐to‐one initiatives after the first year (e.g., Swallow, ), teachers in this study remained committed to mobile learning. When teachers assign pedagogical value to mobile devices, they are more likely to facilitate their implementation in teaching and learning (Praag & Sanchez, ). Nevertheless, participants expressed the need for continuous learning.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers often hold a negative view of wbmt use in the classroom and tend to regard its use as a shortcut that links them directly to their l1 and leads to cognitive disengagement from the language learning process (Van Praag & Sanchez, 2015). Thus, it comes as little surprise that past studies have commonly focused on preventing the inappropriate use of wbmt (Fountain & Fountain, 2009;Steding, 2009).…”
Section: Web-based Machine Translation As Language Learning Toolsmentioning
confidence: 99%
“…The obvious and highly concerning downside to using wbmt for the purpose of language learning is that it can enable students to shift from cognitively engaged language learning processes to simply typing l1 sentences into the computer and mindlessly scribing the results. For such reasons, teachers are often inclined to regard their students' use of wbmt as laziness (Van Praag & Sanchez, 2015) and can experience frustrations when expected to invest their time providing corrective feedback for the output of a machine (Steding, 2009). On the other hand, however, prohibiting the use of wbmt based solely on the assumption that students are incapable of critically analyzing their outputs could be depriving them of a potentially valuable language learning tool.…”
mentioning
confidence: 99%
“…In addition to the widespread use of smartphones, they have been praised for their pedagogical potential, according to a study published by UNESCO [8]; this includes the ability to personalize learning, to extend educational practices and experiences beyond classrooms, and to allow for both informal and teacher-assisted (hybrid) learning. The ongoing expansion of smartphone use has sparked increasing interest by CALL/MALL (computer-assisted language learning/mobile-assisted language learning) researchers and practitioners, with most studies emphasizing their potential for a mobile-assisted L2 pedagogy [6,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%